Remote recruitment and onboarding of public administration employees during the COVID-19 pandemic - Czopek, Miłosz; Kazusek, Marta (Zdalna rekrutacja i onboarding pracowników administracji publicznej w dobie pandemii COVID-19, 2021)
During the fight against the coronavirus, public administration has struggled with the same problems as the private sector, reducing the scope of services provided and extending administrative deadlines. The pandemic has forced organizations to change drastically the way they operate. The necessary modifications of the applied procedures should also include recruitment and onboarding processes. The article presents the results of extensive research conducted at the end of 2020 in public administration bodies located in the Dolnośląskie Voivodeship regarding the impact of the pandemic on the recruitment and adaptation processes. The study shows the forms and tools used, and the scale of their implementation in offices. The results of the verification of the impact of the size of the organization on transforming the selection and onboarding processes of new local government employees are also discussed
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 1 (59), s. 60-69
Keywords: remote recruitment; remote onboarding; COVID-19; public administration; zdalna rekrutacja; zdalny onboarding; administracja publiczna